Economic globalisation and social policy reform: Social work curricula in the South African context - Sewpaul, V (Social Work/Maatskaplike Werk, 2001)
With rapid development of information technology, global influences on policy, education and practice have increased rapidly over recent decades. While social and public policies reflect the values, traditions and ideology of any particular nation, they also reflect the pragmatic constraints of current socio-political and economic realities. There are several compelling reasons for social workers to understand how macro-economic polices impact on welfare. Social work, as a core human service discipline, is often left to pick up the consequences of macro-socio-political and economic policies as they impact directly on people's lives at the micro-level. It is widely accepted that it is people's lives that become structurally adjusted through the processes involved in economic globalisation, structural adjustment policies and debt repayments. However, social policy remains a largely neglected area both in social work training and in social work practice (Ife , 1997; Tembo, 1993, Cox, 1992) . This paper critiques some of the current welfare formulations in South Africa vis-a-vis the Reconstruction and Development Programme (RDP) (ANC, 1994), the White Paper for Social Welfare (Department of Welfare and Population Development, 1997) and Growth, Employment and Redistribution (GEAR) (Ministry of Finance, 1996) and presents empirical data from South African schools of social work in respect of the extent to which curricula interrogate the relationship between these policy formulations and the relationship between economic globalisation and social policy reforms. Data for the empirical study were collected via a mailed questionnaire which was completed by the head of the school/department ( or the person deputised to do so on his/her behalf) of Social Work at South African universities. Twenty questionnaires were sent out, with a response rate of sixty percent, despite two follow-up requests to have the questionnaire completed and returned. The presentation of the empirical data is preceded by defining globalisation, a discussion on the African experience of globalisation and structural adjustment programmes . The paper concludes with a discussion on the implications of economic globalisation for social work practice.